Resource Assessment of a Floating Solar Photovoltaic (FSPV) System with Artificial Intelligence Applications in Lake Mainit, Philippines - Dellosa, J.; Palconit, E. V. (Engineering, Technology & Applied Science Research, 2022)
The Floating Solar Photovoltaic (FSPV) system is an emerging solar PV installation, gaining traction primarily due to its distinct advantages over other forms of installations. FSPV mainly solves the problem when land area is scarce and the power plant capacity is on the megawatt (MW) scale. This paper investigates the resource potential of FSPV, specifically in Lake Mainit, Caraga Region, Philippines. This study implemented a descriptive research design to identify the resources needed to implement an FSPV system in the said lake. The Lake Mainit area can generate 762.96MWh per year. Accounting for the needs of the community, the resources needed to put up the FSPV should satisfy the 35,640Whr daily energy requirement of the community. Based on the analysis, the computed FSPV system size is 9.90kWp. The components required to implement an Artificial Intelligence (AI) integrated monitoring and data processing system for fault diagnosis and detection to help mitigate impact to the FSPV system with the undesirable weather conditions were also identified.